2022
DOI: 10.1161/jaha.121.024814
|View full text |Cite
|
Sign up to set email alerts
|

Incremental Prognosis by Left Atrial Functional Assessment: The Left Atrial Coupling Index in Patients With Floppy Mitral Valves

Abstract: Background Emerging data suggest important prognostic value to left atrial (LA) characteristics, but the independent impact of LA function on outcome remains unsubstantiated. Thus, we aimed to define the incremental prognostic value of LA coupling index (LACI), coupling volumetric and mechanical LA characteristics and calculated as the ratio of left atrial volume index to tissue Doppler imaging a′, in a large cohort of patients with isolated floppy mitral valve. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…28 Consequently, while LA volume and the parameters derived from LA volume are reliable indices of LA function, they may not be able to capture the entirety of LA mechanics. 13 The interdependency of LA and LV strains observed in our study has been previously reported. 29 Our results suggest that the contribution of MAD to LA strain is independent of LV longitudinal function.…”
Section: La Function In Mvp: a Complex Interplay With Madsupporting
confidence: 84%
“…28 Consequently, while LA volume and the parameters derived from LA volume are reliable indices of LA function, they may not be able to capture the entirety of LA mechanics. 13 The interdependency of LA and LV strains observed in our study has been previously reported. 29 Our results suggest that the contribution of MAD to LA strain is independent of LV longitudinal function.…”
Section: La Function In Mvp: a Complex Interplay With Madsupporting
confidence: 84%
“…Left atrial coupling index (LACI) (represented by the ratio between LA volume index and tissue Doppler myocardial velocity during atrial contraction), emerged as a strong and independent determinant of the outcome under non-surgical treatment. LACI ≥ 5 was identified as a threshold for excess mortality ( 42 ). The novel finding that LA functional assessment is a meaningful marker of clinical outcomes underscores the need to standardize the atrial function assessment beyond morphology.…”
Section: Is There Any Consequence Of Volume Overload?mentioning
confidence: 99%
“…LA function provides information (40). Among asymptomatic patients with preserved LVEF, both peaks of atrial longitudinal strain and reservoir strain may predict adverse outcomes (41). Left atrial coupling index (LACI) (represented by the ratio between LA volume index and tissue Doppler myocardial velocity during atrial contraction), emerged as a strong and independent determinant of the outcome under nonsurgical treatment.…”
Section: Addressing the Left Atriummentioning
confidence: 99%
“… 4 Such individual variability in LA response to MR remains poorly defined in term of genetic mechanisms 5 but is remarkable in that LA dilatation severity is highly predictive of long-term outcome, 6 independently of all the baseline characteristics, particularly of those linked to LA enlargement. 7 Furthermore, the intrinsic LA function is now measurable and is even more strongly associated with long-term outcome than LA enlargement, in all types and degrees of MR. 8 , 9 Thus, LA characteristics are truly crucial to consider, particularly in patients with MR.…”
mentioning
confidence: 99%
“… 21 Although LA volume measurements are now widely accepted, LA functional assessment and the degree of fibrosis affecting the atrial wall warrant consistent evaluation. 8 , 9 , 22 A-FMR represents a sizable proportion of MR, 13 the most frequent valve disease affecting the population, 23 and the transition from LA enlargement to FMR warrants analysis in large cohorts. A-FMR is a troubling entity with modest regurgitant volume and a small left ventricle of generally normal function but nevertheless is associated with excess mortality and high incidence of heart failure.…”
mentioning
confidence: 99%